The Relationship Level Between The Player And The Coach And Its Impact On The Achievement Motivation Of The Player - سلمان ريم محمد (Latakia University Journal -Medical Sciences Series, 2022)
This study aimed to identify the relationship level between the player and the coach and its impact on the achievement motivation of the player, In games like (Athletics, football, table tennis, tennis, boxing and gymnastics).The project sample consisted of 64 players from both genders, members of the Syrian Sports Federation in Lattakia, who are all aged between (13-18) years, and randomly chosen.The researcher used the descriptive approach, which is the most suitable approach for this kind of study. The relationship scale between the player and the trainer, was built by the researcher, depending on theoretical literature and his experience as a player, and the achievement motivation scale, which was used as a tool for collecting data.The data were analysed using the following statistical treatments: arithmetical averages and standard deviations, correlation coefficient Pearson. The results of the study indicated a positive correlation but weak between the relationship level between the player and the coach on one hand, and the level of motivation for achievement on the other hand.